Third International Congress on Information and Communication Technology ICICT 2018, London - Yang, Xin-She.; Sherratt, Simon; Dey, Nilanjan; Joshi, Amit.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book includes selected high-quality research papers presented at the Third International Congress on Information and Communication Technology held at Brunel University, London on February 27-28, 2018. It discusses emerging topics pertaining to information and communication technology (ICT) for managerial applications, e-governance, e-agriculture, e-education and computing technologies, the Internet of Things (IOT), and e-mining. Written by experts and researchers working on ICT, the book is suitable for new researchers involved in advanced studies.
Security and Privacy of Things: Regulatory Challenges and Gaps for the Secure Integration of Cyber-Physical Systems -- Cure for Healthcare? Using Drone Technology in Hospital Processes - An Explorative Analysis -- Security Mediated Certi-cateless Undeniable Signature Scheme -- TU framework in automatic formatting a digital library -- Innovative Synthesizer Model for Acoustic Guitar Notes -- Architecture for Cloud-based Industrial Automation -- Information Privacy Violations in Ephemeral Communications -- Fine-Grained Integration of Priority Control and Relay Selection for Fast and Reliable Inter-Vehicle Communication.
Keywords: Telecommunication; Data mining; Data protection; Communications Engineering, Networks; Data Mining and Knowledge Discovery; Data and Information Security